Pendampingan Pengelolaan Keuangan Keluarga Bagi Calon Pengantin Untuk Mengatur Anggaran Rumah Tangga Dan Pencatatan Akuntansi Dengan Metode Kas Kecil Untuk Mengatur Keuangan Keluarga - Rr. Puruwita Wardani; Julius F Nagel (PeKA: Jurnal Pengabdian Kepada Masyarakat, 2019)
Financial planning in the household is very important for couples who are going to build a household. A planned income management as well as expenditure will be able to build a healthy household. Unhealthy finances will easily disrupt household harmony. Thus assistance for the prospective bride and groom to provide provision for family financial planning is very important. This household finance provision includes the introduction of foundation pillars in managing household finances and the introduction of petty cash to manage household financial income and expenditure. The old habit, which says that income minus income equals saving, must be replaced by a new habit, namely income minus savings equals expenditure